Evaluation of Salt-water Intrusion in the Coastal Area of Igbokoda, Southwestern Nigeria - A. O, Talabi; C. A, Ajayi; L. O, Afolagboye; A. A, Oyedele; O. F, Ojo; S. W, Olofinlade (International Journal of Scientific Research and Management (IJSRM), 2018)
Saltwater intrusion into the coastal aquifer has long been recognized as a major threat to groundwater quality around the world. Groundwater evaluation of salt water intrusions in Igbokoda coastal area, southwestern Nigeria was carried out employing combined Horizontal Profiling and Vertical electrical sounding. Two traverses each with two sounding points were occupied. The result from the survey revealed 4 to 5 major layers comprising the unconsolidated silty sand and sandy clay (overburden), clayey zone, consolidated sand zone, partly intruded salt water intruded sandy clay zone and salt water intruded clay zone. The curves were the complex types KQH, KHA, QH and HKH curves. The overburden has resistivity that ranged from 253 to 1316.7Ω-m, thickness that ranged from 0.2 m to 7m. The clayey zone had resistivity of 846.0 Ω-m and thickness of 4m. The consolidated sand zone had resistivity that ranged from 2848.7 to 2865.7Ω-m and thickness that ranged between 4 and 21m. The partly intruded salt water zone is characterized by resistivity that varies between 18.4Ω-m and 93.0Ω-m and thickness of about 7-25m. The salt water intruded zone is characterized by resistivity that ranges between 4.1Ω-m and 9.7Ω-m and thickness of 4-48m. The partly-salt water intruded zones and salt water intruded zone were characterized with low resistivity while the high resistivity zones of consolidated sand layer constitute fresh water bearing zone that could serve as boreholes in the study area.